Choosing an exchange rate regime : the challenge for smaller industrial countries - Argy, Victor E.; Grauwe, Paul de.; Polak, J. J.; International Monetary Fund. (Washington, D.C. : International Monetary Fund ; [Louvain, Belgium?] : Katholieke Universiteit Leuven ; [Sydney, N.S.W.?] : Macquarie University, 1990)
The book consists of Seminar Papers and the associated discussants' comment from a conference held at the Centre for European Policy Studies in Brussels, Oct. 1989. Some papers dealt with analytical issues, while country reviews were undertaken by leading experts on these countries. It is hoped that this volume should serve as an up-to-date review of, and as a basis and inspiration for, continuing work on exchange rate regimes.
Papers from a conference held at the Centre for European Policy Studies in Brussels, Oct. 1989.
Includes bibliographical references.
rpm 19/06/2016; usc 22/5/18
Loans
Keywords: Foreign exchange; Foreign exchange administration; Exchange rate regime